Koanga de Frederick Delius : cherche premier opéra afro-américain désespérément - Benoît Depardieu (Revue LISA)
Although Gershwin’s Porgy & Bess (1935) is still regarded by most critics as the first African-American opera, Louis Gruenberg’s The Emperor Jones (1933) and Scott Joplin’s Treemonisha (1910) have recently challenged this sacrosanct position. Today, according to some researchers, Frederick Delius’s Koanga, based upon the central episode of the story of “Bras coupé” in George Cable’s The Grandissimes, composed in 1897 but whose première took place in 1904, could claim to be “actually the first”. This statement obviously raises the question of the definition of an “African–American” and the attendant criteria. Through an analysis of the libretto as well as the reviews of the various performances from the late 1890’s to the early 1970’s, this article aims to assess the African-American criteria of Koanga.